2019
DOI: 10.1029/2019jb017376
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Study of FeO2Hx Solid and Melt System at High Pressures: Implications for Ultralow‐Velocity Zones

Abstract: Pyrite-type FeO 2 H x (P phase) has recently been suggested as a possible alternative to explain ultralow-velocity zones due to its low seismic velocity and high density. Here we report the results on the congruent melting temperature and melt properties of P phase at high pressures from first-principles molecular dynamics simulations. The results show that P phase would likely be melted near the core-mantle boundary. Liquid FeO 2 H x has smaller density and smaller bulk sound velocity compared to the isochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…The results of recent experimental studies suggest that subducted plates may deliver surface water to the deep lower mantle via CaCl 2 ‐type hydrous phases (Duan et al, 2018; Nishi et al, 2014, 2019; Ohira et al, 2014; Panero & Caracas, 2017; Sano et al, 2008; Tsuchiya, 2013; Walter et al, 2015) and pyrite‐type iron‐hydroxide FeO 2 H x (Liu et al, 2017; Nishi et al, 2017). These deep subducted hydrous phases may release water at the bottom of the mantle (Deng et al, 2019; Nishi et al, 2017; Piet et al, 2020) and/or form some reaction layers at the core‐mantle boundary via active interaction with iron from the core (Liu et al, 2017; Mao et al, 2017; Ohtani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results of recent experimental studies suggest that subducted plates may deliver surface water to the deep lower mantle via CaCl 2 ‐type hydrous phases (Duan et al, 2018; Nishi et al, 2014, 2019; Ohira et al, 2014; Panero & Caracas, 2017; Sano et al, 2008; Tsuchiya, 2013; Walter et al, 2015) and pyrite‐type iron‐hydroxide FeO 2 H x (Liu et al, 2017; Nishi et al, 2017). These deep subducted hydrous phases may release water at the bottom of the mantle (Deng et al, 2019; Nishi et al, 2017; Piet et al, 2020) and/or form some reaction layers at the core‐mantle boundary via active interaction with iron from the core (Liu et al, 2017; Mao et al, 2017; Ohtani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The ULVZs exhibit 5%-20% reductions in compressional wave velocities (V P ) and 10%-30% reductions in shear wave velocities (V S ) compared to the surrounding mantle (McNamara et al, 2010;Thorne & Garnero, 2004), but a 5%-20% increase in density (Idehara, 2011;Reasoner & Revenaugh, 2000;Rost et al, 2005). Several mechanisms for the origin of ULVZs have been proposed, including: (a) partial melting due to high temperatures near the CMB (Andrault et al, 2012;Revenaugh & Meyer, 1997;Williams & Garnero, 1996), (b) isolated remnants of ancient subducted slabs (Dobson & Brodholt, 2005), (c) crystallization products from a basal magma ocean (Labrosse et al, 2007), and (d) enrichment of dense iron-rich phases (Deng et al, 2019;J. Liu et al, 2017;W.…”
Section: Introductionmentioning
confidence: 99%
“…The ULVZs exhibit 5%–20% reductions in compressional wave velocities (V P ) and 10%–30% reductions in shear wave velocities (V S ) compared to the surrounding mantle (McNamara et al., 2010; Thorne & Garnero, 2004), but a 5%–20% increase in density (Idehara, 2011; Reasoner & Revenaugh, 2000; Rost et al., 2005). Several mechanisms for the origin of ULVZs have been proposed, including: (a) partial melting due to high temperatures near the CMB (Andrault et al., 2012; Revenaugh & Meyer, 1997; Williams & Garnero, 1996), (b) isolated remnants of ancient subducted slabs (Dobson & Brodholt, 2005), (c) crystallization products from a basal magma ocean (Labrosse et al., 2007), and (d) enrichment of dense iron‐rich phases (Deng et al., 2019; J. Liu et al., 2017; W. L. Mao et al., 2006; Mergner et al., 2021; Wicks et al., 2010, 2017). Recent geodynamical modeling suggested that ULVZs located close to the edges of thermochemical piles in the lower mantle are most likely caused by compositionally distinct materials, whereas partial melting is possible only in the hottest regions of the piles (M. Li et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of this approach depends largely on the thermodynamic conditions at which it is applied [48]. A wide variety of systems has been explored under the assumption of ideal mixing [49][50][51][52][53][54][55][56]. The hypothesis works remarkably well for hydrocarbon mixtures in the warm dense matter regime [57], water-hydrogen mixtures [58], as well as in hydrogen-helium mixtures enriched in heavier elements [17,33,59,60].…”
Section: Introductionmentioning
confidence: 99%